2023
DOI: 10.1021/acs.est.3c01154
|View full text |Cite
|
Sign up to set email alerts
|

Charge, Aspect Ratio, and Plant Species Affect Uptake Efficiency and Translocation of Polymeric Agrochemical Nanocarriers

Abstract: An incomplete understanding of how agrochemical nanocarrier properties affect their uptake and translocation in plants limits their application for promoting sustainable agriculture. Herein, we investigated how the nanocarrier aspect ratio and charge affect uptake and translocation in monocot wheat (Triticum aestivum) and dicot tomato (Solanum lycopersicum) after foliar application. Leaf uptake and distribution to plant organs were quantified for polymer nanocarriers with the same diameter (∼10 nm) but differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…These findings offered valuable insights into the structure optimization of ATP-site-directed kinase inhibitors for developing treatments against infectious and cancer diseases. In addition, it is worth noting that while hydroponically grown plants easily get access to necessary nutrients and organic pollutants, the trends in the uptake and transport of organic pollutants in hydroponic plants are generally similar to soil cultured plants . Thus, our finding of the promoted BUVS accumulation in rice plants due to the excess stomatal openness has important implications to the bioaccumulation of BUVSs in rice grains and, thus, their exposure to populations through rice consumption.…”
Section: Environmental Implicationsmentioning
confidence: 59%
“…These findings offered valuable insights into the structure optimization of ATP-site-directed kinase inhibitors for developing treatments against infectious and cancer diseases. In addition, it is worth noting that while hydroponically grown plants easily get access to necessary nutrients and organic pollutants, the trends in the uptake and transport of organic pollutants in hydroponic plants are generally similar to soil cultured plants . Thus, our finding of the promoted BUVS accumulation in rice plants due to the excess stomatal openness has important implications to the bioaccumulation of BUVSs in rice grains and, thus, their exposure to populations through rice consumption.…”
Section: Environmental Implicationsmentioning
confidence: 59%
“…The majority of the reported hydrodynamic radii of these carriers are due to these hydrated blocks. The interactions between the “soft” macromolecular star polymer and the lipid bilayers of protoplasts could reasonably be different from the less soft FNP particles, given these differences in structure and properties …”
Section: Resultsmentioning
confidence: 99%
“…Overall, it suggests that to benefit designing NMs for agriculture, a systematic assessment of transportation efficiency of charged nanoparticles by considering the proper control of size, charge, shape, surface coating, application methods, plant species (dicots and monocots, C3 and C4 plants) is an urgent task. Indeed, a recent study showed that the total transport of nanocarrier is different between monocot plants (∼3 to 9%, wheat) and dicot plants (8–25%, tomato), and also the wheat but not tomato plant has the limitation of size cutoff for high aspect ratio nanocarriers (300 nm long) …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study showed that the total transport of nanocarrier is different between monocot plants (∼3 to 9%, wheat) and dicot plants (8−25%, tomato), and also the wheat but not tomato plant has the limitation of size cutoff for high aspect ratio nanocarriers (300 nm long). 65 Furthermore, for rational design of NMs for agriculture, besides the above-mentioned criterion, more attention should be paid to the leaf phyllosphere, such as the microbiome at the leaf surface. These microbes live either inside (endosphere) or outside (episphere) of plant tissues and play important roles in the ecology and physiology of plants.…”
mentioning
confidence: 99%